APIP CAPABILITY ANALYSIS IN NORTH SUMATRA INSPECTORATE - Nine Rihaney; Hafidz Tigor Barita; Deliana (UPT Publikasi Ilmiah UNISBA, 2023)
This research is motivated by the importance of increasing the capability of the Government Internal Supervisory Apparatus (APIP) in achieving effective internal control to achieve good organizational governance. This study aims to determine the factors that influence APIP capability, namely to determine the effect of HR competence, leadership commitment and budget on APIP capability. The object of this research is The Inspectorate of North Sumatra Province. This research is a case study research. The results of the study show that HR competence, leadership commitment and budget play a very important role in enhancing APIP's capabilities in achieving effective internal control to achieve good organizational governance.. Keywords: APIP's Capability, Competence, Leadership Commitment, Budget.